Keberlanjutan Usahatani Padi Sawah di Wilayah Daerah Aliran Sungai (DAS) Paguyaman Kabupaten Boalemo - Rauf, Asda (Universitas Galuh, 2024)
Wetland rice cultivation becomes crucial in sustaining the food supply amidst various challenges related to land use conversion. Given this issue, it is essential to assess the suitability and capacity of the land so that land production factors can become more efficient. This is also related to the establishment of sustainable agriculture. This research aims to analyze the sustainability of wetland rice farming in the Paguyaman River Basin region of Boalemo Regency, considering ecological, economic, institutional, and technological aspects. The study was conducted using a quantitative approach with a descriptive method among farmers in the Paguyaman and Wonosari Districts of Boalemo Regency. The data for this research consisted of primary data collected through questionnaires, interviews, and field observations. The questionnaire used in this research employed the Multidimensional Scaling (MDS) model. The subjects of this study included 30 respondents. The data analysis employed the Localization Index (LI), Specialization Index (SI), and sustainability analysis using the Multiaspect Sustainability Analysis (MSA) program. The research results indicate that the Localization Index (LI) is 0.3877, categorized as spread out, with a Specialization Index (SI) of 1.1094, categorized as specialized. Furthermore, the sustainability of wetland rice as a commodity is categorized as